Polishing method of optical glass lens and cerium oxide polishing powder

By polishing the cerium oxide polishing liquid made of specific cerium oxide polishing powder, the problems of poor uniformity of polishing powder and dangerous process in the prior art are solved, and the polishing effect is achieved with high efficiency, environmental protection and long-life.

CN119505707APending Publication Date: 2025-02-25DEMETER SUZHOU ELECTRONICS ENVIRONMENTAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620522.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing cerium-based rare earth polishing powder has poor uniformity, high non-rare earth impurities content, dangerous process operation, unfriendly environment, and the impact of acid ions and metal ions introduced during the polishing process on product purity, making it difficult to meet the requirements of high surface quality and long life.

Method used

The cerium oxide polishing liquid made of specific cerium oxide polishing powder is used for polishing. By directly using the cerium chloride rare earth liquid produced by rare earth manufacturers, strong acids are avoided. High-temperature reactions and the addition of polyethylene glycol are used to control the grain morphology and particle refinement, and the chemical activity and cutting force of the polishing powder are improved.

Benefits of technology

It achieves excellent polishing quality, high polishing efficiency, better safety and environmental protection, and long polishing life, reducing production costs and improving environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505707A_ABST
    Figure CN119505707A_ABST
Patent Text Reader

Abstract

The invention discloses a polishing method of an optical glass lens and cerium oxide polishing powder.The polishing method comprises the working procedure of preparing a cerium oxide polishing solution and the working procedure of polishing the optical glass lens through the cerium oxide polishing solution, and the cerium oxide polishing solution is formed by dispersing the cerium oxide polishing powder in a solvent; the method for preparing the cerium oxide polishing powder comprises the following steps: at 55-65 DEG C, continuously adding a carbonate precipitator into cerium chloride rare earth feed liquid, reacting until the pH value of a system reaches 6.0-6.5 to obtain rare earth carbonate slurry, purifying, adding polyethylene glycol with proper molecular weight, stirring and aging, heating to 90 DEG C or above, and preserving heat; after the heat preservation is finished, carrying out filter pressing, drying, calcining, carrying out water cooling, and carrying out ball milling; according to the method, the cerium oxide polishing solution prepared from the specific cerium oxide polishing powder is used for polishing the optical glass lens, so that the polishing quality is excellent, the polishing efficiency is high, the safety and the environmental protection property are better, and the polishing life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing, in particular to the polishing of optical glass lenses, and specifically to a polishing method for optical glass lenses and cerium oxide polishing powder. Background Art

[0002] It is known that the hardness of cerium-based rare earth polishing powder is close to that of optical glass, and it can be prepared into polishing slurry to process the surface of optical glass lenses. The performance of polishing powder determines the quality of optical glass lenses to a certain extent. At present, the preparation methods of cerium-based rare earth polishing powder mainly include the following two methods:

[0003] The first method is to directly calcine, crush, and classify cerium carbonate in which cerium-based rare earth oxides account for 98.0wt.% or more of the total amount of rare earth oxides;

[0004] The second method is to use lanthanum carbonate cerium rare earth raw materials to strengthen acid dissolution, and then use liquid phase precipitation method to add precipitant or fluorinating agent to prepare fluorinated rare earth carbonate, and then do subsequent calcination, particle size crushing, etc.

[0005] However, in practice, the pure cerium oxide rare earth polishing powder prepared by the first method has poor uniformity, a high content of non-rare earth impurities, sharp edges and corners of the particles, which are easily scratched and difficult to meet the requirements of high surface quality and long life. The process route of the second method involves strong acid, is highly dangerous to operate, is environmentally unfriendly, and has low overall economic benefits.

[0006] In addition, with the continuous advancement of science and technology, the demand for ultra-high precision optical glass lenses is increasing. As optical glass lenses are used in more demanding and cutting-edge experimental environments, not only low roughness and high flatness are required for optical glass lenses, but also the introduction of new acid ions and metal ions in the polishing process should be reduced as much as possible (the presence of acid ions may corrode equipment, and metal ions may have a serious impact on the application of the product). This puts higher requirements on the purity of the polishing products of polished optical glass lenses. However, the current cerium-based rare earth polishing powder still has more or less the problem of insufficient purity. Summary of the invention

[0007] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved method for polishing optical glass lenses. The method uses a cerium oxide polishing liquid made from a specific cerium oxide polishing powder to polish the optical glass lenses. The method not only has excellent polishing quality and high polishing efficiency, but also has better safety and environmental protection and a long polishing life.

[0008] The present invention also provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method can directly use cerium chloride rare earth liquid directly produced by a rare earth manufacturer, has relatively low cost, and avoids the step of using strong acid to dissolve cerium carbonate rare earth, which is both economical and environmentally friendly and safe.

[0009] In order to achieve the above object, a technical solution adopted by the present invention is:

[0010] A polishing method for an optical glass lens, the polishing method comprising the steps of preparing a cerium oxide polishing liquid and polishing the optical glass lens using the cerium oxide polishing liquid, wherein the cerium oxide polishing liquid is formed by dispersing cerium oxide polishing powder in a solvent;

[0011] Wherein, the method for preparing the cerium oxide polishing powder comprises:

[0012] At the first temperature, continuously adding a carbonate precipitant to the cerium chloride rare earth solution to react until the pH value of the system reaches 6.0-6.5, thereby obtaining a rare earth carbonate slurry;

[0013] Adjust the Cl in the rare earth carbonate slurry - The content is less than or equal to 30ppm, polyethylene glycol with an average molecular weight of 3000-8000 is added, stirred and aged, and then the temperature is raised to the second temperature and kept warm;

[0014] The rare earth carbonate slurry after heat preservation is filtered and dried to obtain a pretreated material;

[0015] The pretreated material is calcined at 1000-1100° C., water-cooled after calcination, and ball-milled;

[0016] The first temperature is 55-65°C, and the second temperature is greater than or equal to 90°C.

[0017] According to some preferred aspects of the present invention, the second temperature is greater than or equal to 95°C.

[0018] In some preferred embodiments of the present invention, the second temperature is 95-99°C.

[0019] According to some preferred aspects of the present invention, the second temperature is kept warm for 30-200 min. Further, the second temperature is kept warm for 30-150 min. Further, the second temperature is kept warm for 50-100 min.

[0020] In some preferred embodiments of the present invention, in the cerium chloride rare earth feed solution, the cerium-based rare earth oxide accounts for more than 99.995wt.% of the total amount of rare earth oxides, except for Cl -In addition, the content of other non-rare earth impurities is less than 50 ppm. Further, in some embodiments, the concentration of cerium-based rare earth oxide in the cerium chloride rare earth solution can be greater than or equal to 280 g / L.

[0021] In some preferred embodiments of the present invention, the cerium chloride rare earth feed solution is purified before the carbonate precipitant is added, and the concentration of the cerium-based rare earth oxide is controlled to be 80-120 g / L. Further, the purification can be performed by filtering with a filter press to remove non-rare earth impurities such as solid particle precipitation and floating matter that may exist therein, preferably obtaining a clear, transparent, and nearly colorless cerium chloride rare earth feed solution.

[0022] According to some preferred aspects of the present invention, the carbonate precipitant is ammonium carbonate and / or ammonium bicarbonate. This type of precipitant can reduce the introduction of impurities and can escape in the form of carbon dioxide, ammonia, etc. at a later stage, thereby reducing the content of impurities in the system.

[0023] In some embodiments of the present invention, the carbonate precipitant is added in the form of an aqueous carbonate precipitant solution. Further, the concentration of the aqueous carbonate precipitant solution is 1.0-3.5 mol / L.

[0024] According to some specific aspects of the present invention, the method for preparing the rare earth carbonate slurry includes:

[0025] Selecting cerium chloride rare earth liquid from a rare earth raw material manufacturer as the raw material for synthesizing cerium carbonate rare earth;

[0026] First, a filter press is used to remove non-rare earth impurities such as solid particle precipitation and floating objects; the clarified rare earth chloride feed liquid is added into a synthesis reactor with a heating jacket, and deionized water is added to dilute the cerium-based rare earth oxide concentration of the cerium chloride rare earth feed liquid to 80-120g / L, and the feed liquid is heated to 55-65°C after dilution, and then a carbonate precipitant aqueous solution is added. During the addition of the precipitant, the flow rate should be controlled and added at a uniform speed, so that no foam overflows during the precipitation process. During the whole process, the change of pH value is monitored in real time, and the flow rate should be reduced when the pH value is close to the reaction end point. When the pH value of the precipitant addition end point is 6.0-6.5, the addition of the precipitant is stopped.

[0027] In the present invention, strictly controlling the pH value at the end point of the precipitation reaction can ultimately control the content of impurities such as calcium, magnesium, iron, silicon, etc. in the synthetic material.

[0028] According to some preferred and specific aspects of the present invention, before adding the polyethylene glycol, the rare earth carbonate slurry is treated as follows:

[0029] The rare earth carbonate slurry is filtered to remove part of the water, and then washed with water until the Cl -The content is less than or equal to 30 ppm, and then part of the water is removed to obtain a first filter cake with a content of cerium-based rare earth oxide greater than or equal to 45.0 wt.%;

[0030] The first filter cake is crushed and added to water to be evenly dispersed. The above operation of filtering the rare earth carbonate slurry to remove part of the water is conducive to washing away the impurities contained in the slurry during water washing, and the first filter cake is then dispersed with water, which is conducive to the transportation of intermediate materials and other operations.

[0031] According to some preferred aspects of the present invention, the temperature of the water used for washing is 50-70°C, which is conducive to removing impurities such as Cl in the slurry. - If the temperature is too low, a lot of water will be needed for a long time to flush; if the temperature is too high, energy will be wasted. The maximum allowable feed temperature of the plate and frame of the plate and frame filter press is less than 75°C.

[0032] According to some preferred aspects of the present invention, in the process of adding the obtained first filter cake into water after crushing, the mass ratio of the first filter cake to the water is 1:0.95-1.10.

[0033] According to some preferred aspects of the present invention, after the first filter cake is crushed and added to water, a surfactant is added; the amount of the surfactant added is 0.5%-3.0% of the cerium-based rare earth oxide in the first filter cake. In the present invention, the addition of the surfactant can disperse the material faster and save production time.

[0034] In some embodiments of the present invention, the surfactant is a combination of one or more selected from polyacrylamide, polyacrylamide, and polyvinyl pyrrolidone.

[0035] In some preferred embodiments of the present invention, the polyethylene glycol is a combination of one or more selected from polyethylene glycol-4000 (PEG-4000 for short), polyethylene glycol-6000 (PEG-6000 for short) and polyethylene glycol-8000 (PEG-8000 for short).

[0036] According to some preferred aspects of the present invention, the amount of polyethylene glycol added is 0.1 wt.%-1.0 wt.% of the cerium-based rare earth oxide in the first filter cake.

[0037] According to some preferred aspects of the present invention, the stirring and aging time is 0.5-3h.

[0038] According to some preferred aspects of the present invention, the calcination time is 4-10 hours.

[0039] According to some preferred aspects of the present invention, the implementation method of preparing the pretreated material includes: filtering the rare earth carbonate slurry after the insulation to obtain a second filter cake with a cerium-based rare earth oxide content greater than or equal to 45.0wt.%, and then flash drying to control the moisture content of the material to be less than or equal to 3.0wt.%.

[0040] According to some preferred aspects of the present invention, in the process of preparing the cerium oxide polishing powder, after calcination, the calcined material is cooled to 500-600°C, and then mixed with water in a mass ratio of 1:0.8-1.2 for water cooling, the cooled water-material mixture is ball-milled, and additives are added during the ball milling process until the ball milling is to the expected particle size, and then freeze-dried to control the water content of the material to be less than 2.0wt.%.

[0041] In the present invention, water cooling is used for rapid temperature reduction, which can increase the defect energy of grains in the powder, increase the chemical activity of the polishing powder, and further enhance the cutting force of the polishing powder.

[0042] In some embodiments of the present invention, the auxiliary agent includes polyacrylic acid (the addition amount accounts for 0.1wt.%-0.8wt.% of the cerium oxide polishing powder) and carboxymethyl cellulose (the addition amount accounts for 0.5wt.%-2.0wt.% of the cerium oxide polishing powder).

[0043] According to some preferred and specific aspects of the present invention, the expected particle size is: D 50 0.4-0.8μm, D 97 Less than 4.5μm.

[0044] In some embodiments of the present invention, the freeze drying is to pre-freeze the material at -30 to -50°C for 2 to 8 hours, and then dry it at a vacuum pressure of 0.1 to 1 Pa for 4 to 12 hours.

[0045] According to some preferred aspects of the present invention, in the process of polishing an optical glass lens with the cerium oxide polishing liquid, the upper plate rotation speed of the polishing machine is 10-20 rpm, and the upper plate pressure is 120-140 kg.

[0046] In some embodiments of the present invention, the polishing machine is a 9B double-sided grinder.

[0047] According to some preferred aspects of the present invention, the solvent is water.

[0048] Another technical solution provided by the present invention is a method for preparing cerium oxide polishing powder, the preparation method comprising:

[0049] At the first temperature, continuously adding a carbonate precipitant to the cerium chloride rare earth solution to react until the pH value of the system reaches 6.0-6.5, thereby obtaining a rare earth carbonate slurry;

[0050] Adjust the Cl in the rare earth carbonate slurry - The content is less than or equal to 30ppm, polyethylene glycol with an average molecular weight of 3000-8000 is added, stirred and aged, and then the temperature is raised to the second temperature and kept warm;

[0051] The rare earth carbonate slurry after heat preservation is filtered and dried to obtain a pretreated material;

[0052] The pretreated material is calcined at 1000-1100° C., water-cooled after calcination, and ball-milled;

[0053] The first temperature is 55-65°C, and the second temperature is greater than or equal to 90°C.

[0054] Another technical solution provided by the present invention is: cerium oxide polishing powder prepared by the preparation method of cerium oxide polishing powder described above.

[0055] Another technical solution provided by the present invention is an application of the cerium oxide polishing powder described above in polishing optical glass lenses.

[0056] In some embodiments of the present invention, the optical glass lens comprises k9 glass.

[0057] Generally speaking, the composition of K9 glass is roughly as follows: SiO2, B2O3, BaO, Na2O, K2O, As2O3.

[0058] In some cases, in k9 glass, SiO2 accounts for about 69.13wt.%, B2O3 accounts for about 10.75wt.%, BaO accounts for about 3.07wt.%, Na2O accounts for about 10.40wt.%, K2O accounts for about 6.29wt.%, and As2O3 accounts for about 0.36wt.%.

[0059] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0060] The present invention is based on the defects of existing optical glass lenses in the process, such as poor polishing effect, short polishing life, high cost of polishing liquid and unfriendly environment, and innovatively provides an improved optical glass lens polishing method. The method adopts cerium oxide polishing powder prepared by a specific method as a polishing abrasive. Specifically: (1) During the liquid phase synthesis process, it is unexpectedly found that the addition of polyethylene glycol with an average molecular weight of 3000-8000 changes the growth direction of the crystal surface of the polishing powder after calcination, changes the morphology of the polishing powder grains, and can improve the polishing yield. Practice shows that the use of polyethylene glycol with a larger molecular weight will cause a large amount of uncontrollable foam to be generated during the experiment, and the experiment cannot be carried out. If polyethylene glycol with a smaller molecular weight is used, the grain morphology we aim for will not be achieved. In addition, the product of the present invention has a relatively high requirement on purity. Many compounds containing metal ions cannot be used. Another part of organic compounds that do not contain metal ions are acidic and will react with rare earth carbonate to release CO2, which is not what we expect.

[0061] (2) It has been found in practice that a higher reaction temperature, such as a high temperature reaction greater than 90°C, can refine the particles of the overall material and reduce the time consumed by the subsequent ball milling; it can also make the polyethylene glycol with an average molecular weight of 3000-8000 more evenly attached to the surface of cerium carbonate, making the morphology of the grains more consistent and rounded, and the particles of the material tend to be more spherical, all of which greatly improve the yield of the polishing powder; at the same time, it can also promote a substantial increase in the size of the cerium oxide grains in the later calcined material, greatly improving the overall polishing life of the polishing powder;

[0062] In the present invention, a cerium chloride rare earth feed liquid is heated to 55-65°C and a carbonate precipitant is added to synthesize cerium carbonate rare earth first, and then polyethylene glycol with an average molecular weight of 3000-8000 is added after impurity removal, and the temperature is raised to above 90°C for high-temperature reaction after aging. The main reason for the staged reaction is that if the cerium chloride rare earth feed liquid is heated to above 90°C and then a carbonate precipitant is added during the operation, serious foaming will occur during the reaction process, and the preparation process is difficult to control; and the synthesized material has a small particle size and a large viscosity, which makes it difficult to wash with water in the later stage, and the water consumption is large. - The content is difficult to control below 30ppm.

[0063] In summary, the method of the present invention uses a cerium oxide polishing liquid made of a specific cerium oxide polishing powder to polish an optical glass lens, which not only has excellent polishing quality and high polishing efficiency, but also has better safety and environmental protection and a long polishing life. In addition, the present invention can directly use the cerium chloride rare earth feed liquid directly produced by the rare earth manufacturer, which has a relatively low cost and avoids the step of using a strong acid to dissolve the cerium carbonate rare earth, which is both economical and environmentally safe. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a scanning electron microscope image of the material sampled and dried after being processed in step (4) in Example 1;

[0065] Figure 2 This is a scanning electron microscope image of the material sampled and dried after being processed in step (4) in Example 2;

[0066] Figure 3 This is a scanning electron microscope image of the material sampled and dried after being treated in step (4) in Example 3;

[0067] Figure 4 This is a scanning electron microscope image of a sample of the material obtained after treatment in step (4) in Example 4 after drying;

[0068] Figure 5 This is a scanning electron microscope image of a sample of the material obtained after treatment in step (4) in Example 5 after drying;

[0069] Figure 6 This is a scanning electron microscope image of the material sampled and dried after being treated in step (4) in Example 6;

[0070] Figure 7 This is a scanning electron microscope image of the material sampled and dried after being treated in step (4) in Comparative Example 1;

[0071] Figure 8 This is a scanning electron microscope image of the material sampled and dried after being treated in step (4) in Comparative Example 2;

[0072] Fig. 9 This is a scanning electron microscope image of the material sampled and dried after being treated in step (4) in Comparative Example 3;

[0073] Fig.10 This is a scanning electron microscope image of a sample of the material obtained after treatment in step (4) in comparative example 4 and after drying. DETAILED DESCRIPTION

[0074] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0075] Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art. In the following, REO concentration refers to the concentration of cerium-based rare earth oxides.

[0076] Example 1

[0077] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0078] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2 g / L, heating the feed liquid to about 60° C. after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1 mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of the pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0079] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is - The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0080] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is fully stirred and dispersed uniformly, and then PEG-4000 (PEG-4000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, After stirring and aging for 2 hours, the material is then heated to 97±1°C and maintained at this temperature for 90 minutes; the rare earth carbonate slurry after insulation is pumped into a filter press by a slurry pump to filter out excess water to obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, the second filter cake with excess water removed is crushed and sent to a flash dryer to fully dry the second filter cake, the moisture content of the material at the main discharge port is monitored, and sampling is performed every 3 hours until the moisture content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0081] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 1 As shown;

[0082] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.67μm,D 97 :3.45μm;

[0083] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0084] Example 2

[0085] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0086] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2g / L, heating the feed liquid to about 55°C after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0087] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is -The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0088] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is fully stirred and dispersed uniformly, and then PEG-4000 (PEG-4000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, After stirring and aging for 2 hours, the material is then heated to 97±1°C and maintained at this temperature for 90 minutes; the rare earth carbonate slurry after insulation is pumped into a filter press by a slurry pump to filter out excess water to obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, the second filter cake with excess water removed is crushed and sent to a flash dryer to fully dry the second filter cake, the moisture content of the material at the main discharge port is monitored, and sampling is performed every 3 hours until the moisture content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0089] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 2 As shown;

[0090] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.63μm,D 97 :3.55μm;

[0091] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0092] Example 3

[0093] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0094] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2g / L, heating the feed liquid to about 65°C after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of the pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0095] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is - The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0096] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is fully stirred and dispersed uniformly, and then PEG-4000 (PEG-4000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, After stirring and aging for 2 hours, the material is then heated to 97±1°C and maintained at this temperature for 90 minutes; the rare earth carbonate slurry after insulation is pumped into a filter press by a slurry pump to filter out excess water to obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, the second filter cake with excess water removed is crushed and sent to a flash dryer to fully dry the second filter cake, the moisture content of the material at the main discharge port is monitored, and sampling is performed every 3 hours until the moisture content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0097] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 3 As shown;

[0098] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.64μm,D 97 :3.46μm;

[0099] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0100] Example 4

[0101] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0102] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2 g / L, heating the feed liquid to about 60° C. after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1 mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of the pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0103] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is -The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0104] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is stirred and dispersed evenly, and then PEG-6000 (PEG-6000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, After stirring and aging for 2 hours, the material is then heated to 97±1°C and maintained at this temperature for 90 minutes; the rare earth carbonate slurry after insulation is pumped into a filter press by a slurry pump to filter out excess water to obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, the second filter cake with excess water removed is crushed and sent to a flash dryer to fully dry the second filter cake, the moisture content of the material at the main discharge port is monitored, and sampling is performed every 3 hours until the moisture content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0105] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 4 As shown;

[0106] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.68μm,D 97 :3.43μm;

[0107] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0108] Example 5

[0109] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0110] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2 g / L, heating the feed liquid to about 60° C. after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1 mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of the pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0111] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is - The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0112] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is stirred and dispersed evenly, and then PEG-8000 (PEG-8000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, After stirring and aging for 2 hours, the material is then heated to 97±1°C and maintained at this temperature for 90 minutes; the rare earth carbonate slurry after insulation is pumped into a filter press by a slurry pump to filter out excess water to obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, the second filter cake with excess water removed is crushed and sent to a flash dryer to fully dry the second filter cake, the moisture content of the material at the main discharge port is monitored, and sampling is performed every 3 hours until the moisture content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0113] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 5 As shown;

[0114] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.70μm,D 97 :3.55μm;

[0115] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0116] Example 6

[0117] This example provides a method for preparing cerium oxide polishing powder and the prepared cerium oxide polishing powder. The method for preparing the cerium oxide polishing powder comprises:

[0118] (1) Selecting cerium chloride rare earth feed liquid (purchased from Baotou Huamei Rare Earth High-Tech Co., Ltd., brand CeCl3-3N5A) from a rare earth raw material manufacturer as a raw material for synthesizing cerium carbonate rare earth; firstly removing non-rare earth impurities such as solid particle precipitation and floating matter therein by filtering with a filter press; adding the clarified rare earth chloride feed liquid into a synthesis reactor with a heating jacket, adding deionized water to dilute the REO concentration of the cerium chloride rare earth feed liquid to 88±2g / L, heating the feed liquid to about 65°C after dilution, and then adding an ammonium bicarbonate aqueous solution, the concentration of which is 2.7±0.1mol / L, and controlling the flow rate of the precipitant to be added at a uniform speed during the addition of the precipitant, so that no foam overflows during the precipitation process, and monitoring the change of the pH value in real time during the whole process, reducing the flow rate when the pH value is close to 6.0, and stopping the addition of the precipitant when the pH value is 6.5, to obtain a cerium carbonate rare earth slurry;

[0119] (2) The cerium carbonate rare earth slurry synthesized in step (1) is pumped into a filter press by a slurry pump to filter out excess water, and then deionized water at a temperature of 60° C. is introduced to rinse until the Cl in the material is -The content is less than or equal to 30 ppm, and then the excess water is removed by filtration to obtain a first filter cake having a cerium-based rare earth oxide content greater than or equal to 45.0 wt.%;

[0120] (3) The first filter cake from which excess water is removed in step (2) is crushed and added to a reactor containing deionized water (the mass ratio of the first filter cake to the deionized water in the reactor is 1:1), and then a surfactant (specifically sodium polyacrylate, the addition amount is 1.0 wt.% of the cerium-based rare earth oxide in the first filter cake) is added, and the mixture is stirred and dispersed evenly, and then PEG-4000 (PEG-4000 is added in the form of an aqueous solution with a mass concentration of 10%) is slowly added to the mixture. After the addition is completed, Stir and age for 2 hours, then heat the material to 97±1°C and maintain the temperature for 120 minutes; pump the rare earth carbonate slurry after insulation into a filter press with a slurry pump, filter out excess water, and obtain a second filter cake with a cerium-based rare earth oxide content of greater than or equal to 45.0wt.%, crush the second filter cake with excess water removed and send it to a flash dryer, fully dry the second filter cake, monitor the water content of the material at the main discharge port, and take samples every 3 hours until the water content of the material at the main discharge port is less than or equal to 3.0wt.%;

[0121] (4) The flash dried material is placed in a sagger and sent into a kiln, where it is heated for calcination. When the temperature reaches the highest temperature within the range of 1030°C ± 10°C, it is kept warm for 7 hours. After the calcination is completed, the material is cooled to 550 ± 10°C and then mixed with water in a mass ratio of 1:1 for water cooling. The SEM image of the obtained material after drying is shown in FIG. Figure 6 As shown;

[0122] (5) The water-material mixture after water cooling is transported to a high-energy vibration mill. During the ball milling process, polyacrylic acid (accounting for 0.5wt.% of the cerium oxide rare earth polishing powder) is added to accelerate the grinding effect. The material particle size is monitored by a Horiba 960 laser particle size analyzer until the expected particle size is obtained. After the ball milling is completed, the particle size in the slurry is: D 50 :0.61μm,D 97 :3.45μm;

[0123] (6) The polishing slurry obtained after ball milling is freeze-dried, the material is pre-frozen at -40°C for 4 hours, and dried at a vacuum pressure of 0.5 Pa for 8 hours. The moisture content of the powder after drying is controlled to be less than 2.0%. The powder is cerium oxide rare earth polishing powder.

[0124] Comparative Example 1

[0125] The process is basically the same as Example 1, except that in step (3), the material is heated to 35±1°C.

[0126] The SEM image of the material sampled and dried after the treatment in step (4) is shown in Figure 7 As shown in the figure, it shows that when the material temperature is low, the edges and corners of the grain morphology are sharp.

[0127] Comparative Example 2

[0128] The process is basically the same as Example 1, except that in step (3), the material is heated to 60±1°C.

[0129] The SEM image of the material sampled and dried after the treatment in step (4) is shown in Figure 8 As shown in the figure, it shows that as the temperature increases, the edges and corners of the grain morphology become blunt and begin to grow towards a spherical shape, but the temperature of 60°C is still not enough.

[0130] Comparative Example 3

[0131] The process is basically the same as Example 1, except that PEG-4000 is not added in step (3).

[0132] The SEM image of the material sampled and dried after the treatment in step (4) is shown in Fig. 9 As shown in the figure, it shows that without adding PEG4000, the edges and corners of the grain morphology are very sharp.

[0133] Comparative Example 4

[0134] The method is basically the same as Example 1, except that in step (3), PEG-4000 is replaced with PEG-400 of the same added mass.

[0135] The SEM image of the material sampled and dried after the treatment in step (4) is shown in Fig.10 As shown in the figure, it shows that the PEG with too small molecular weight has a relatively weak effect on the edge blunting of the grain morphology, and there are still stepped edges on the grain surface.

[0136] Application Example 1

[0137] This example provides a polishing method for an optical glass lens, the polishing method comprising a process of preparing a cerium oxide polishing liquid and a process of polishing the optical glass lens using the cerium oxide polishing liquid;

[0138] The cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Example 1 in deionized water;

[0139] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min and the upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.78 wire / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was 98.9% (after polishing, the glass was ultrasonically cleaned and dried, wiped with alcohol and observed with the naked eye under a 200-lumen strong light. If there was no scratch, it was considered to meet the requirements, and the same applies to the following).

[0140] The polishing method was further tested, and the service life of the polishing liquid was tested after 150 sets of continuous polishing (taking into account the volatility of the equipment, the polishing thinning amount in each set of tests varied within 10%, and the service life was considered to be unchanged).

[0141] Application Example 2

[0142] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Example 2 in deionized water.

[0143] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min. The upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.76 wire / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was: 98.1%. The polishing method was further tested. The service life of the polishing liquid was 147 groups of continuous polishing.

[0144] Application Example 3

[0145] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Example 3 in deionized water.

[0146] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min. The upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.77 wire / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was: 98.5%.

[0147] The polishing method was further tested and the service life of the polishing liquid was 152 sets of continuous polishing.

[0148] Application Comparative Example 1

[0149] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Comparative Example 1 in deionized water.

[0150] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min. The upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.82 wires / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was: 69.44%.

[0151] Application Comparative Example 2

[0152] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Comparative Example 2 in deionized water.

[0153] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min. The upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.80 wire / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was: 78%.

[0154] Application Comparative Example 3

[0155] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Comparative Example 3 in deionized water.

[0156] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polisher was 15r / min. The upper plate pressure of the polisher was 130kg. The polishing reduction of the k9 glass was measured to be 0.81 wire / 12 minutes (the average reduction value of 12 pieces of glass). The glass surface yield was 68.9%.

[0157] Application Comparative Example 4

[0158] The method is basically the same as Example 1, except that the cerium oxide polishing liquid with a solid content of 15% is prepared by dispersing the cerium oxide polishing powder prepared in Comparative Example 4 in deionized water.

[0159] The k9 glass was polished on a 9B double-sided grinding machine. Each group polished 12 pieces of flat glass. The polishing time was 12 minutes. The upper plate speed of the polishing machine was 15r / min. The upper plate pressure of the polishing machine was 130kg. The polishing thinning of the k9 glass was measured to be 0.80 wire / 12 minutes (the average thinning value of 12 pieces of glass). The glass surface yield was 83.5%.

[0160] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0161] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for polishing an optical glass lens, characterized in that: The polishing method comprises the steps of preparing a cerium oxide polishing liquid and polishing an optical glass lens with the cerium oxide polishing liquid, wherein the cerium oxide polishing liquid is formed by dispersing cerium oxide polishing powder in a solvent; Wherein, the method for preparing the cerium oxide polishing powder comprises: At the first temperature, continuously adding a carbonate precipitant to the cerium chloride rare earth solution to react until the pH value of the system reaches 6.0-6.5, thereby obtaining a rare earth carbonate slurry; Adjust the Cl in the rare earth carbonate slurry - The content is less than or equal to 30ppm, polyethylene glycol with an average molecular weight of 3000-8000 is added, stirred and aged, and then heated to the second temperature and kept warm; The rare earth carbonate slurry after heat preservation is filtered and dried to obtain a pretreated material; The pretreated material is calcined at 1000-1100° C., water-cooled after calcination, and ball-milled; The first temperature is 55-65°C, and the second temperature is greater than or equal to 90°C.

2. The method for polishing an optical glass lens according to claim 1, characterized in that: The second temperature is greater than or equal to 95°C.

3. The polishing method of an optical glass lens according to claim 2, characterized in that: The second temperature is 95-99°C.

4. The polishing method for an optical glass lens according to claim 1, 2 or 3, characterized in that: The temperature is maintained at the second temperature for 30-200 minutes.

5. The method for polishing an optical glass lens according to claim 1, characterized in that: In the cerium chloride rare earth liquid, the cerium-based rare earth oxide accounts for more than 99.995wt.% of the total amount of rare earth oxides, except for Cl - In addition, the content of other non-rare earth impurities is less than 50ppm.

6. The method for polishing an optical glass lens according to claim 5, characterized in that: Before adding the carbonate precipitant, the cerium chloride rare earth solution is purified, and the concentration of the cerium-based rare earth oxide is controlled to be 80-120 g / L.

7. The method for polishing an optical glass lens according to claim 1, characterized in that: The carbonate precipitant is ammonium carbonate and / or ammonium bicarbonate; and / or the carbonate precipitant is added in the form of an aqueous solution of the carbonate precipitant with a concentration of 1.0-3.5 mol / L.

8. The method for polishing an optical glass lens according to claim 1, characterized in that: Before adding the polyethylene glycol, the rare earth carbonate slurry is treated as follows: The rare earth carbonate slurry is filtered to remove part of the water, and then washed with water until the Cl - The content is less than or equal to 30 ppm, and then part of the water is removed to obtain a first filter cake with a content of cerium-based rare earth oxide greater than or equal to 45.0 wt.%; The obtained first filter cake is crushed and added into water and dispersed evenly.

9. The method for polishing an optical glass lens according to claim 8, characterized in that: The temperature of the water used for the flushing is 50-70°C.

10. The method for polishing an optical glass lens according to claim 8, characterized in that: In the process of adding the crushed first filter cake into water, the mass ratio of the first filter cake to the water is 1:0.95-1.

10.

11. The method for polishing an optical glass lens according to claim 8, characterized in that: After the obtained first filter cake is crushed and added into water, a surfactant is added; the added amount of the surfactant accounts for 0.5%-3.0% of the cerium-based rare earth oxide in the first filter cake.

12. The method for polishing an optical glass lens according to claim 11, characterized in that: The surfactant is a combination of one or more selected from polyacrylamide, polyacrylamide and polyvinyl pyrrolidone.

13. The method for polishing an optical glass lens according to claim 8, characterized in that: The amount of polyethylene glycol added is 0.1 wt. % to 1.0 wt. % of the cerium-based rare earth oxide in the first filter cake.

14. The method for polishing an optical glass lens according to claim 1 or 13, characterized in that: The polyethylene glycol is a combination of one or more selected from polyethylene glycol-4000, polyethylene glycol-6000 and polyethylene glycol-8000.

15. The method for polishing an optical glass lens according to claim 1, characterized in that: The stirring and aging time is 0.5-3h; and / or the calcination time is 4-10h.

16. The method for polishing an optical glass lens according to claim 1, characterized in that: The implementation method of preparing the pretreated material includes: filtering the rare earth carbonate slurry after heat preservation to obtain a second filter cake with a cerium-based rare earth oxide content greater than or equal to 45.0wt.%, and then flash drying to control the moisture content of the material to be less than or equal to 3.0wt.%; and / or, in the process of preparing the cerium oxide polishing powder, after calcination, cooling the calcined material to 500-600°C, and then mixing it with water at a mass ratio of 1:0.8-1.2 for water cooling, ball milling the cooled water-material mixture, adding an additive during the ball milling process until the ball milling reaches the expected particle size, and then freeze drying to control the moisture content of the material to be less than 2.0wt.%; wherein the expected particle size is: D 50 0.4-0.8μm, D 97 Less than 4.5μm.

17. The method for polishing an optical glass lens according to claim 1, characterized in that: In the process of polishing an optical glass lens with the cerium oxide polishing liquid, the upper plate rotation speed of the polishing machine is 10-20 rpm, the upper plate pressure is 120-140 kg; and / or the solvent is water.

18. A method for preparing cerium oxide polishing powder, characterized in that: The preparation method comprises: At the first temperature, continuously adding a carbonate precipitant to the cerium chloride rare earth solution to react until the pH value of the system reaches 6.0-6.5, thereby obtaining a rare earth carbonate slurry; Adjust the Cl in the rare earth carbonate slurry - The content is less than or equal to 30ppm, polyethylene glycol with an average molecular weight of 3000-8000 is added, stirred and aged, and then heated to the second temperature and kept warm; The rare earth carbonate slurry after heat preservation is filtered and dried to obtain a pretreated material; The pretreated material is calcined at 1000-1100° C., water-cooled after calcination, and ball-milled; The first temperature is 55-65°C, and the second temperature is greater than or equal to 90°C.

19. Cerium oxide polishing powder prepared by the method for preparing cerium oxide polishing powder according to claim 18.